LEADER FOLLOWER DISTANCE WITHIN THE ORGANIZATIONS: OVERVIEW AND SCALE ADAPTATION STUDY (Third Sector Social Economic Review, 2023)
The growth of organizations and developments in the technology causes leaders and followers work in wider areas and brings distance between them. This distance is effecting the perceptions of the followers about the leader and intra-organizational relations. Despite its importance, leader follower distance studies in Turkey are scarce. In this study, after giving the theoretical framework of leader follower distance, Turkish version of the leader follower distance scale, which can be used as a measurement tool in industrial/organizational psychology studies, has been validated. The study includes adapting the original scale to Turkish, testing internal consistency; performing exploratory and confirmatory factor analysis and doing criterion-dependent validity study with data collected from two samples. As a result, three-dimensional structure of the scale was validated to be used in Turkey.
Keywords: Leader-follower distance; physical distance; social distance; relational distance; scale; validation study